Combined Cycle Performance Deterioration Analysis - Zwebek, A. I. (Cranfield University, 2002)
Combined cycles are subject to degradations and hence performance deterioration. According to the author's survey nothing was found in the open literature on this subject. Therefore, it was anticipated that it would be of great achievement if a tool for analysing and diagnosing the deterioration of combined cycle could be produced. So this thesis presents a procedure for combined cycle performance analysis and fault diagnostic by way of simulation. l order to accomplish this task successfully it was necessary to developed two pieces of software. These are STEAMOMATCH for steam cycle performance deterioration analysis, and GOTRESS for GPA of any system. STEAMOMATCH, which is built on the basics of combined cycle thermodynamics, can simulate up to three levels of pressure with reheat. On the other hand GOTRESS uses a Gas Path Analysis technique that enables the user the choice of conducting either linear or non-linear GPA at the same time. I both cases single or multiple fault can be diagnosed. GOTRESS was built in such a way that it makes it a generalised code that can be used not only for combined cycle but to diagnose a wide range of power cycle plants. The deterioration simulation results of the gas turbine power plant showed that the isentropic efficiency deterioration of the turbine unit has the uppermost sever effect on overall gas turbine power output and thermal efficiency. This is also the case with steam turbine (bottoming) cycle power and Rankine efficiency. Also, the simulation results obtained showed that the relationship between the gas turbine size and its performance deterioration is almost constant, i.e. performance deterioration follows the plant's size. Among the two major gas turbine parameters that affects the steam bottoming cycle performance of a CCGT power plant, the gas turbine exhaust temperature has a predominant effect on steam cycle efficiency over the exhaust mass flow.' As a general result, the obtained simulation results showed that the behaviour of CCGT power plant performance is more affected by gas turbine cycle conditions than by steam turbine cycle conditions. The obtained results showed that GPA can be successfully applied to either gas turbine cycle, steam turbine cycle, or the combination of the two in a form of combined cycle. The GPA diagnostic results obtained showed that it would be possible to detect some faults that might occur within the gas turbine that is a part of a combined cycle power plant by monitoring the dependent parameters of the steam turbine (bottoming) cycle such as live steam pressure and temperature and steam turbine power. In contrast, it would not been possible to detect the problems (implanted faults) that might occur within the steam turbine by monitoring the dependent parameters of the gas turbine unit.